Analisa Laju Pelepasan Kalor Kondensor 10 U dan Separation Condenser Dengan Penambahan Subcooler Terhadap Koefisien Prestasi Mesin Pendingin Refrigerator Menggunakan Refrigerant Liquefied Petroleum Gas - Amirul Yahya; Franciscus Xaverius Kristianta; Nasrul Ilminnafik (Jurnal Energi dan Teknologi Manufaktur, 2019)
The research used an experimental method by comparing the use of condenser separation with addition subcooler and condenser 10 U. In the same process condensation was done with the same condenser length with varying refrigerant discharge of 114x10-6 m3/s, 131x10-6 m3/s and 148x10-6 m3/s. The study used a refrigerant LPG (Liquefied Petroleum Gas) with a composition of 50% butane and propane 50%. The objective of study was to analyze heat release rate values ​​of both condensers on the coefficient of machine / COP (Coefficient of Performance) value of the refrigerator. Research on the 114x10-6 m3/s refrigerant discharge resulted in average of heat release rate separation condenser with addition subcooler higher than 10 U condenser with value of 0.000455727 kW. Refrigerant discharge test 131x10-6 m3/s, the average of heat release rate separation condenser with addition subcooler is higher than the condenser 10 U of 0.000297211 kW. Refrigerant discharge test 148x10-6 m3/s, condenser 10 U yields average of heat release rate value higher than separation condenser with addition subcooler amount of 0,014013777 kW. The average value of heat release rate by the condenser 10 U will have the same trend value of COP, while at the separation condenser with addition subcooler yielding a value which is inversely proportional to the COP yield, the lower of heat release rate the resulting COP value will increase.